The Insights and Illusions of Consumption Measurements - Battistin, Erich (World Bank, Washington, DC, 2020)
Although household well-being is anchored in long-term average rates of consumption, welfare comparisons typically rely on shorter-duration survey measurements. This paper develops a new strategy to identify the distribution of these long-term rates by leveraging a large-scale randomization that elicited repeated short-duration measurements from diaries and recall questions. Identification stems from diary-recall differences in reports from the same household, does not require these reports to be error-free, and hinges on a research design with broad replicability. This strategy delivers cost-effective suggestions for designing survey modules to yield the most accurate measurements of consumption well-being, and offers new insights for interpreting and reconciling diary-recall differences in household expenditure surveys.